Silicon-tin composite material, preparation method thereof, pole piece and battery

Through the multi-layered silicon-tin composite material, the problem of insufficient electrochemical performance of the negative electrode material of lithium-ion battery is solved, high energy density and excellent cycling performance are achieved, and the needs of high energy density and portable equipment are met.

CN119297239APending Publication Date: 2025-01-10NINGBO SHANSHAN NEW MATERIAL TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411413649.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The electrochemical performance of the existing lithium-ion battery anode material, silicon-tin composite, has not yet reached its maximum potential, especially in terms of cycle performance and Coulomb efficiency, which cannot meet the needs of high energy density and portable electronic devices.

Method used

The silicon-tin composite material adopts a multi-layer clad structure, including the core of porous silicon material, the first clad layer is a carbon layer, the second clad layer is nanotin particles, and the third clad layer is a nitrogen-doped carbon layer, The fourth cladding layer is a chestnut-shaped carbon layer, prepared by solvent gel method and chemical bath deposition method to optimize the pore structure and electrical conductivity of the material.

Benefits of technology

The capacity performance, circulation performance and Coulomb efficiency of the battery have been significantly improved. The first discharge specific capacity reaches more than 2350mAh/g, the capacity retention rate of 200 cycles exceeds 85%, and the first effect reaches more than 93.5%. The material is easy to obtain and simple to prepare.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297239A_ABST
    Figure CN119297239A_ABST
Patent Text Reader

Abstract

The invention discloses a silicon-tin composite material and a preparation method thereof, a pole piece and a battery. The silicon-tin composite material sequentially comprises an inner core, a first coating layer, a second coating layer, a third coating layer and a fourth coating layer from inside to outside, the inner core comprises a silicon material, the first coating layer is a carbon layer, the second coating layer comprises nano tin particles, the third coating layer is a carbon layer, and the fourth coating layer is a chestnut-shaped carbon layer. The silicon-tin composite material disclosed by the invention has excellent conductivity and relatively low charge transfer internal resistance, and a battery assembled by the silicon-tin composite material has excellent capacity performance, cycle performance and coulombic efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a silicon-tin composite material and a preparation method thereof, a pole piece and a battery. Background Art

[0002] The shortage of traditional energy and environmental pollution problems have spawned green new energy technologies for environmental protection and sustainable development. Lithium-ion secondary batteries have great development potential in the field of new energy. Commercially, graphite is usually used as the negative electrode of lithium-ion secondary batteries, which has a low theoretical specific capacity of 372mAh / g and cannot well meet the growing energy density requirements and operational reliability requirements of portable electronic devices, electric vehicles and large-scale energy storage applications. Therefore, it is imperative to develop a high-performance negative electrode material to improve the performance of lithium-ion batteries. Among a series of potential alternative materials, silicon, as a new generation of negative electrode materials, has attracted widespread attention from academia and business. Compared with traditional graphite materials, silicon has an ultra-high theoretical specific capacity (4200mAh / g), a slightly higher voltage platform than graphite, better safety performance, and abundant element reserves. As a semiconductor material, silicon has poor conductivity. During the lithium ion insertion and extraction process, the silicon negative electrode will cause huge volume expansion and contraction (>300%), resulting in the crushing of the electrode material, structural collapse, and destruction of ion and electron conduction channels, thereby seriously deteriorating the battery's cycle performance. According to reports from a large number of researchers, technical means such as nanocrystalline silicon technology (such as silicon nanosheets, silicon nanofibers, silicon foam), silicon-carbon composite technology, and silicon alloying technology have achieved certain results in addressing the above-mentioned defects.

[0003] Patent application CN 116565175A introduces a method for preparing a double-shell structure lithium-ion battery negative electrode material. First, waste silica gel is pyrolyzed and ground to obtain white powder; the powder is evenly mixed with tin dioxide and then mixed with water to prepare an aqueous phase dispersion; a carbon source is added under strong stirring until it is completely dissolved without any agglomeration to obtain a dispersion D; then the mixed dispersion D is spray-dried to prepare a pyrolysis precursor, and finally the precursor is pyrolyzed to obtain SiOx@SnO2@C negative electrode material. The first discharge capacity and first efficiency of the negative electrode material are in the range of 540.2-770.2mAh / g and 53.3%-70.3%, respectively. The performance improvement of the composite of silicon and tin by this method is still limited. Therefore, an efficient method is needed to fully maximize the capacity of silicon-tin-based materials and obtain excellent electrochemical performance. Summary of the invention

[0004] The present invention further improves the electrochemical performance of silicon-tin negative electrode materials in the prior art, and proposes a silicon-tin composite material and its preparation method and application, a pole piece and a battery. The silicon-tin composite material of the present invention has excellent electrical conductivity and low charge transfer internal resistance, and a battery assembled from the silicon-tin composite material has excellent capacity performance, cycle performance and coulombic efficiency.

[0005] The present invention adopts the following technical solutions to solve the above technical problems:

[0006] The present invention provides a silicon-tin composite material, which comprises, from the inside to the outside, a core, a first coating layer, a second coating layer, a third coating layer and a fourth coating layer; the core contains silicon material, the first coating layer is a carbon layer, the second coating layer contains nano-tin particles, the third coating layer is a carbon layer, and the fourth coating layer is a chestnut-shaped carbon layer.

[0007] In the present invention, the silicon material is preferably a porous silicon material, such as a mesoporous silicon material, wherein "mesoporous silicon material" means that the pore size of the silicon material is between 2 nm and 50 nm.

[0008] In the present invention, the silicon material is preferably doped with heteroatoms, such as one or more of boron (B), phosphorus (P), nitrogen (N), sulfur (S) and metal heteroatoms.

[0009] In some preferred embodiments of the present invention, the silicon material is a porous silicon material doped with heteroatoms, such as a B and P co-doped porous silicon material.

[0010] In the present invention, preferably, the first coating layer is doped with heteroatoms, such as one or more of nitrogen, boron and phosphorus.

[0011] In the present invention, preferably, the fourth cladding layer is doped with heteroatoms, such as one or more of nitrogen, boron and phosphorus.

[0012] In the present invention, the silicon content in the silicon-tin composite material may be 42%-48%, where the percentage is the mass percentage of silicon element in the silicon-tin composite material.

[0013] In the present invention, the tin content in the silicon-tin composite material may be 12%-17%, where the percentage is the mass percentage of the tin element in the silicon-tin composite material.

[0014] In the present invention, the carbon content in the silicon-tin composite material may be 25%-30%, where the percentage is the mass percentage of carbon element in the silicon-tin composite material.

[0015] In the present invention, the nitrogen content in the silicon-tin composite material may be 0%-2%, where the percentage is the mass percentage of nitrogen element in the silicon-tin composite material.

[0016] In the present invention, the boron content in the silicon-tin composite material may be 0%-1%, where the percentage is the mass percentage of the boron element in the silicon-tin composite material.

[0017] In the present invention, the phosphorus content in the silicon-tin composite material may be 0%-0.5%, where the percentage is the mass percentage of phosphorus element in the silicon-tin composite material.

[0018] In the present invention, the oxygen content in the silicon-tin composite material may be 7%-14%, where the percentage is the mass percentage of oxygen element in the silicon-tin composite material.

[0019] In the present invention, the pore size of the silicon-tin composite material may be 12-21 nm.

[0020] In the present invention, the electrical conductivity of the silicon-tin composite material can be 2.5×10 3 -2.7×10 4 S / m.

[0021] In the present invention, the charge transfer internal resistance of the silicon-tin composite material can be 14-28Ω.

[0022] The present invention provides a method for preparing a silicon-tin composite material, which comprises the following steps:

[0023] S1, coating a carbon layer on the surface of a silicon material to obtain a first precursor;

[0024] S2, mixing the first precursor and a tin source to obtain a second precursor;

[0025] S3, coating the surface of the second precursor with a carbon layer, and forming nano-tin particles from the tin source during the formation of the carbon layer, to obtain a third precursor;

[0026] S4. Coating a chestnut-shaped carbon layer on the surface of the third precursor.

[0027] In the present invention, in step S1, the method for coating the carbon layer can be conventional in the art, preferably a solvent gel method.

[0028] In the present invention, in step S1, the silicon material may be a conventional silicon material in the art. The silicon material is preferably a porous silicon material. The silicon material is preferably a silicon material doped with heteroatoms, wherein the heteroatoms are, for example, one or both of boron (B) and phosphorus (P). The silicon material is more preferably a porous silicon material doped with heteroatoms, for example, a porous silicon material co-doped with B and P.

[0029] In some preferred embodiments of the present invention, in step S1, a carbon layer is coated on the surface of the silicon material by a solvent gel method, comprising the following steps:

[0030] S1-1, ultrasonically dispersing the surfactant in water to form spherical micelles;

[0031] S1-2, adding a carbon source monomer, a nitrogen source and a catalyst, stirring to obtain a sol;

[0032] S1-3, adding silicon material to obtain a core-shell colloid;

[0033] S1-4, heating and polymerization to obtain a silicon material coated with a gel polymer;

[0034] S1-5, carbonization, the gel polymer forms a carbon layer.

[0035] In the present invention, preferably, the surfactant described in step S1-1 is one or more of hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dialkyldimethylammonium chloride and alkyldimethylbenzylammonium bromide.

[0036] Preferably, the molar ratio of the carbon source monomer, nitrogen source and catalyst in step S1-2 to the surfactant in step S1-1 is (1.0-3.0): (0.01-0.09): (0.007-0.03): (0.2-0.65).

[0037] Preferably, the nitrogen source in step S1-2 is one or more of p-nitroaniline, melamine, triethylamine, pyridine, azobis(ethylbutyronitrile) and pyrrole.

[0038] Preferably, the carbon source monomers in step S1-2 include resorcinol and formaldehyde.

[0039] Preferably, the catalyst in step S1-2 is a basic compound.

[0040] Preferably, the alkaline compound in step S1-2 is one or more of sodium carbonate, sodium hydroxide and sodium citrate.

[0041] Preferably, the molar ratio of the silicon material in step S1-3 to the catalyst in step S1-2 is (0.8-1.5):(0.007-0.03).

[0042] Preferably, the polymerization temperature in step S1-4 is 80-100°C.

[0043] Preferably, the polymerization time in step S1-4 is 3-8 hours.

[0044] Preferably, the carbonization method in step S1-5 is heat treatment.

[0045] Preferably, the heat treatment temperature is 450-800°C.

[0046] Preferably, the heat treatment time is 4-10 hours.

[0047] Preferably, a drying step is further included before the carbonization step in step S1-5.

[0048] In the present invention, preferably, in step S2, the mass ratio of the first precursor to the tin source is (85-95): (8-15).

[0049] Preferably, the tin source in step S2 is tin powder and / or tin dioxide powder.

[0050] In step S2, the mixing is preferably performed by ball milling, and more preferably, the ball milling is performed in the presence of an inert gas plasma.

[0051] Preferably, the inert gas is one or more of argon, helium and neon.

[0052] Preferably, the ball milling environment pressure is 0.1 MPa.

[0053] Preferably, the ball-to-material ratio of the ball mill is (40-60):1.

[0054] Preferably, the rotation speed of the ball mill is 650-800r / min.

[0055] Preferably, the ball milling time is 4-8h.

[0056] Preferably, the tube volume of the ball mill is 0.2L.

[0057] Preferably, the working current of the ball mill is 1-3A.

[0058] Preferably, the excitation voltage of the ball mill is 10-25 kV.

[0059] In the present invention, in step S3, the method of coating the carbon layer preferably adopts a solvent gel method.

[0060] In some preferred embodiments of the present invention, in step S3, a carbon layer is coated on the surface of the second precursor by a solvent gel method, comprising the following steps:

[0061] S3-1, ultrasonically dispersing the surfactant in water to form spherical micelles;

[0062] S3-2, adding a carbon source monomer, a nitrogen source and a catalyst, stirring to obtain a sol;

[0063] S3-3, adding the second precursor to obtain a core-shell colloid;

[0064] S3-4, heating and polymerizing to obtain a second precursor coated with a gel polymer;

[0065] S3-5, carbonization, the gel polymer forms a carbon layer, and the tin source forms tin nanoparticles to obtain a third precursor.

[0066] In the present invention, in step S3-1, the surfactant is preferably one or more of hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dialkyldimethylammonium chloride and alkyldimethylbenzylammonium bromide.

[0067] Preferably, the molar ratio of the carbon source monomer, nitrogen source and catalyst in step S3-2 to the surfactant in step S3-1 is (1.0-3.0): (0.01-0.09): (0.007-0.03): (0.2-0.65).

[0068] Preferably, the nitrogen source in step S3-2 is one or more of p-nitroaniline, melamine, triethylamine, pyridine, azobis(ethylbutyronitrile) and pyrrole.

[0069] Preferably, the carbon source monomers in step S3-2 include resorcinol and formaldehyde.

[0070] Preferably, the catalyst in step S3-2 is a basic compound.

[0071] Preferably, the alkaline compound in step S3-2 is one or more of sodium carbonate, sodium hydroxide and sodium citrate.

[0072] Preferably, the molar ratio of the second precursor in step S3-3 to the catalyst in step S3-2 is (0.8-1.5):(0.007-0.03).

[0073] Preferably, the polymerization temperature in step S3-4 is 80-100°C.

[0074] Preferably, the polymerization time in step S3-4 is 3-8 hours.

[0075] Preferably, the carbonization method in step S3-5 is heat treatment.

[0076] Preferably, the heat treatment temperature is 450-800°C.

[0077] Preferably, the heat treatment time is 4-10 hours.

[0078] Preferably, a drying step is further included before the carbonization step in step S3-5.

[0079] In the present invention, in step S4, the coated chestnut-shaped carbon layer is preferably prepared by chemical bath deposition method and sol-gel method.

[0080] In some preferred embodiments of the present invention, in step S4, a chestnut-shaped carbon layer is coated on the surface of the third precursor by a chemical bath deposition method, comprising the following steps:

[0081] S4-1, ultrasonically dispersing the third precursor in a quaternary ammonium salt aqueous solution to obtain a third precursor dispersion; adding an aqueous solution containing a nickel salt and an initiator to the third precursor dispersion, stirring, adding ammonia water, reacting under stirring, centrifuging, and drying to obtain a composite material A;

[0082] S4-2, heat-treating the composite material A and then rapidly cooling it to obtain a composite material B;

[0083] S4-3, adding the composite material B to a surfactant aqueous solution, and sequentially adding a carbon source monomer and an initiator, reacting under stirring, and centrifugally washing and drying to obtain a composite material C;

[0084] S4-4, calcining the composite material C, cooling, and obtaining a composite material D; the composite material D comprises a nickel layer and a carbon layer;

[0085] S4-5. Treat the composite material D with acid to remove the nickel layer, wash, and dry to form a chestnut-shaped carbon layer.

[0086] In the present invention, preferably, the quaternary ammonium salt in step S4-1 is one or more of hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dialkyldimethylammonium chloride and alkyldimethylbenzylammonium bromide.

[0087] Preferably, the mass ratio of the third precursor to the quaternary ammonium salt in step S4-1 is (0.1-0.5): (0.009-0.05).

[0088] Preferably, the nickel salt in step S4-1 is one or more of nickel acetate, nickel nitrate and nickel sulfate.

[0089] Preferably, the initiator in step S4-1 is one or more of potassium persulfate, sodium persulfate and potassium hydrogen persulfate.

[0090] Preferably, the mass ratio of the nickel salt, the initiator and the third precursor in step S4-1 is (0.1-0.5): (0.02-0.1): (0.1-0.5).

[0091] Preferably, the stirring in step S4-1 is performed in an oil bath at 25°C.

[0092] Preferably, the centrifugation time in step S4-1 is 10-30 min, preferably 20 min.

[0093] Preferably, the centrifugal speed in step S4-1 is 200-300 r / min, preferably 260 r / min.

[0094] Preferably, the temperature of the heat treatment in step S4-2 is 350-600°C.

[0095] Preferably, the constant temperature time of the heat treatment in step S4-2 is 2-5 hours.

[0096] Preferably, the heating rate of the heat treatment in step S4-2 is 1-10°C / min.

[0097] The heating rate refers to the heating rate during the process of heating to the heat treatment temperature.

[0098] Preferably, the cooling rate of the rapid cooling in step S4-2 is 15°C / min.

[0099] Preferably, the surfactant in step S4-3 is an anionic surfactant.

[0100] Preferably, the anionic surfactant is one or more of sodium dodecylbenzenesulfonate, hexadecyltrimethylammonium p-toluenesulfonate, sodium dodecylsulfonate and sodium α-olefinsulfonate.

[0101] Preferably, the initiator is one or more of potassium persulfate, sodium persulfate and potassium hydrogen persulfate.

[0102] Preferably, the mass ratio of the surfactant, carbon source monomer and initiator in step S4-3 is (3-10): (0.09-0.3): (0.2-0.65).

[0103] Preferably, the carbon source monomer in step S4-3 is pyrrole and / or pyridine.

[0104] Preferably, the calcination temperature in step S4-4 is 650-850°C.

[0105] Preferably, the calcination time in step S4-4 is 3-6 hours.

[0106] Preferably, the calcination in step S4-4 is performed in an inert atmosphere.

[0107] Preferably, the cooling rate of the cooling in step S4-4 is 15°C / min.

[0108] Preferably, the acid used in the acid treatment in step S4-5 is one or more of hydrochloric acid, sulfuric acid and nitric acid.

[0109] Preferably, the concentration of the acid used in the acid treatment in step S4-5 is 0.05 to 0.2 mol / L.

[0110] In the present invention, before step S1, the following step may be further included: S0, preparing a porous silicon material, wherein the porous silicon material is preferably prepared by a sol-gel method and a magnesium thermal reduction method.

[0111] In some preferred embodiments of the present invention, in step S1, the silicon material is a porous silicon material co-doped with B and P, and the preparation method thereof comprises the following steps:

[0112] S0-1, stirring and ultrasonically dispersing a mixture containing a silicon source, an acid aqueous solution, a phosphorus source and a boron source, and drying to obtain a silicon aerogel;

[0113] S0-2, heat-treating the mixture of the silicon aerogel and the magnesium powder to obtain a porous silicon material precursor;

[0114] S0-3, etching the porous silicon material precursor in an acid aqueous solution to obtain a B and P co-doped porous silicon material.

[0115] In the present invention, preferably, the mass ratio of the silicon source, the acid aqueous solution, the phosphorus source and the boron source in step S0-1 is (2.5-5.5): (0.01-0.06): (0.2-0.6): (0.08-0.15).

[0116] Preferably, the silicon source in step S0-1 is one or more of ethyl orthosilicate, methyl silane orthosilicate, and silicates (such as sodium silicate, potassium silicate, magnesium silicate, and iron silicate).

[0117] Preferably, the acid in the acid aqueous solution in step S0-1 is one or more of hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid and oxalic acid, and the concentration is 0.05 to 0.2 mol / L.

[0118] Preferably, the phosphorus source in step S0-1 is one or more of phytic acid, phosphoric acid and diammonium hydrogen phosphate.

[0119] Preferably, the boron source in step S0-1 is one or more of boric acid, triethyl borate and tripropyl borate.

[0120] Preferably, the temperature of the ultrasonic dispersion in step S0-1 is 40-60°C.

[0121] Preferably, the ultrasonic dispersion time in step S0-1 is 1-3 hours.

[0122] Preferably, the drying temperature in step S0-1 is 80-100°C, preferably 90°C.

[0123] Preferably, the drying time in step S0-1 is 24 hours.

[0124] Preferably, the stirring in step S0-1 is performed in an oil bath at 25°C.

[0125] Preferably, the stirring time in step S0-1 is 1-2.5 h.

[0126] In the present invention, preferably, the mass ratio of the silica aerogel to the magnesium powder in step S0-2 is 1:1.

[0127] Preferably, the temperature of the heat treatment in step S0-2 is 650-850°C.

[0128] Preferably, the heating rate of the heat treatment in step S0-2 is 1-10°C / min.

[0129] Preferably, the heat treatment time in step S0-2 is 2-10 hours.

[0130] Preferably, the heat treatment in step S0-2 is performed under an inert atmosphere.

[0131] Preferably, the inert atmosphere in step S0-2 is one or more of argon, helium, and neon.

[0132] Preferably, the acid in the acid aqueous solution in step S0-3 is one or more of hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid and oxalic acid, and the concentration is 0.05 to 0.2 mol / L.

[0133] Preferably, the etching time in step S0-3 is 4-6 hours.

[0134] Preferably, a drying step is further included after the etching step in step S0-3.

[0135] In the present invention, all drying steps can be carried out in one of the following three ways:

[0136] (1) freeze drying, wherein the freeze drying temperature may be -30°C to -80°C, and the drying time may be 3-7 hours;

[0137] (2) CO2 supercritical drying, wherein the CO2 supercritical drying temperature may be 10-40°C, the pressure may be 10-15 kPa, and the drying time may be 1-3 hours;

[0138] (3) Vacuum drying, wherein the vacuum drying temperature may be 60-90° C., such as 80° C., and the drying time may be 4-20 h.

[0139] The invention provides a silicon-tin composite material prepared by adopting the preparation method of the silicon-tin composite material.

[0140] The present invention also provides a pole piece, which comprises the above silicon-tin composite material.

[0141] Wherein, the electrode sheet is preferably a negative electrode sheet.

[0142] The present invention also provides a battery, which comprises the above-mentioned pole piece.

[0143] In the present invention, the battery is preferably a lithium ion battery.

[0144] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0145] The positive and progressive effects of the present invention are:

[0146] (1) The present invention improves the electrical and electrochemical properties of the silicon-tin composite material by constructing a multi-layer coating structure. The multi-layer carbon coating layer can multiplex the volume expansion of the silicon material, and the introduction of nano-tin particles and chestnut-shaped structures significantly improves the electronic conductivity and reduces the capacity loss.

[0147] (2) The battery assembled from the silicon-tin composite material has excellent capacity performance (the first discharge specific capacity is above 2350 mAh / g), cycle performance (the capacity retention rate is above 85% after 200 cycles at a rate of 0.1C) and first efficiency (above 93.5%).

[0148] (3) The raw materials used in the present invention are easily available and inexpensive, and the preparation method is simple and applicable to existing industrial technologies. BRIEF DESCRIPTION OF THE DRAWINGS

[0149] Figure 1 Schematic diagram of the single particle structure of the silicon-tin composite material obtained in Example 1 of the present invention. 1 is the core, 2 is the silicon material, 3 is the first coating layer, 4 is the nano-tin particle, 5 is the second coating layer, 6 is the third coating layer, and 7 is the fourth coating layer (i.e., the chestnut-shaped carbon layer).

[0150] Figure 2 This is the 200 cycle performance of Example 1 of the present invention at a rate of 0.1C.

[0151] Figure 3 The figure shows the rate performance of Example 1 of the present invention at different rates. DETAILED DESCRIPTION

[0152] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0153] Example 1

[0154] The preparation of the silicon-tin composite material specifically comprises the following steps:

[0155] S0. Preparation of B and P co-element doped porous silicon material:

[0156] S0-1, silane methyl orthosilicate, 0.1 mol / l oxalic acid aqueous solution, phytic acid and triethyl borate were mixed in a mass ratio of 4.5:0.03:0.3:0.1 and stirred for 1.5 h, ultrasonically dispersed at 50°C for 2 h, placed in an oven for 24 h to fix the gel network, and then dried to obtain B and P element doped silica aerogel;

[0157] S0-2, the aerogel and magnesium powder are sent into a tube furnace at a mass ratio of 1:1 for heating, and then heated in a tube furnace at 700°C for 2-10 hours at a heating rate of 3°C / min under an inert atmosphere;

[0158] S0-3. The obtained powder was etched in a 1 mol / L hydrochloric acid aqueous solution for 5 h to remove by-products (magnesium oxide and a small amount of Mg2Si), and then vacuum dried at 80°C for 6 h to obtain a B and P co-element doped porous silicon material.

[0159] S1. Preparation of multi-atom doped encapsulated porous silicon precursor (first precursor):

[0160] S1-1, octadecyltrimethylammonium chloride (0.35 mmol) was dispersed by ultrasonication to be uniformly distributed in deionized water (10 mol), and spherical micelles were formed and fixed;

[0161] S1-2, secondly, adding a mixture of 0.06 mmol nitroaniline, resorcinol (R, 0.8 mmol), formaldehyde (F, 0.8 mol) and 0.01 mmol sodium carbonate, and continuously stirring to obtain a surface-stabilized sol;

[0162] S1-3, then, 1.5 mmol of doped porous silicon precursor was added to obtain a surfactant-stabilized core-shell colloid;

[0163] S1-4, then polymerizing the core-shell colloid at 85° C. for 6 h to obtain an encapsulated sol polymer;

[0164] S1-5. The obtained encapsulated sol polymer is vacuum dried at 80°C for 6 hours, and then heat treated at 550°C for 5 hours in an argon atmosphere to carbonize the gel polymer; during the heat treatment, the sol polymer is carbonized into a spherical carbon shell to obtain a multi-atom doped encapsulated porous silicon precursor.

[0165] S2. Preparation of tin-doped carbon-encapsulated porous silicon precursor (second precursor): Place the multi-atom doped encapsulated porous silicon precursor and tin powder in a ball mill at a mass ratio of 85:8, apply vacuum sealing grease to the rubber ring of the end cover of the ball mill and the rubber ring of the electrode rod shoulder, and complete the ball mill packaging. Evacuate the ball mill through the vacuum valve, and then fill it with argon gas with a gauge pressure of 0.1 MPa, and repeat 3 times, finally making the environmental condition in the ball mill an inert gas of about 0.1 MPa; ball-to-material ratio of 60:1, ball mill speed of 750 r / min, ball mill time of 6 h, ball mill tube volume of 0.2 L; working current of 1-3 A, excitation voltage of 10-25 kV, and efficiently synthesize uniform tin-doped carbon-encapsulated porous silicon precursor through the synergistic effect of argon plasma and grinding balls.

[0166] S3. Preparation of nitrogen-doped multilayer carbon encapsulated porous silicon precursor (third precursor):

[0167] S3-1, 0.35 mmol of octadecyltrimethylammonium chloride was evenly dispersed in deionized water (10 mol) by ultrasonic dispersion, and spherical micelles were formed and fixed;

[0168] S3-2, then, add 0.06mmol nitroaniline, resorcinol (R, 0.8mmol), formaldehyde (F, 0.8mol) and 0.01mmol sodium carbonate, and continue stirring to obtain a surface-stable sol;

[0169] S3-3, then, 1.5 mmol of tin-doped carbon encapsulated porous silicon precursor was added to obtain a surfactant-stabilized core-shell colloid;

[0170] S3-4, polymerizing the core-shell colloid at 85° C. for 7 h to obtain a sol polymer encapsulated by a silicon-tin alloy;

[0171] S3-5. The obtained silicon-tin alloy encapsulated sol polymer is vacuum dried at 80°C for 6 hours, and then heat treated at 650°C for 5 hours in an argon atmosphere to carbonize the gel polymer; during the heat treatment, the sol polymer is carbonized into a spherical carbon shell, and the tin layer becomes molten, and then rapidly cooled at a rate of 60°C / min to form tin nanoparticles, thereby obtaining a nitrogen-doped multilayer carbon encapsulated porous silicon precursor.

[0172] S4. Preparation of encapsulated core-shell structured silicon-tin composite material:

[0173] S4-1, add 0.1g of nitrogen-doped multilayer carbon-encapsulated porous silicon precursor to 50mL of deionized water dissolved with 0.01g of hexadecyltrimethylammonium bromide, stir, and ultrasonically treat for 45min to make the nitrogen-doped multilayer carbon-encapsulated porous silicon precursor well distributed and preserved; dissolve 0.11g of nickel acetate and 0.021g of sodium persulfate in another 50mL of distilled water; after complete dissolution, slowly add to the nitrogen-doped multilayer carbon-encapsulated porous silicon precursor dispersion; after stirring for 45min, add 20mL of 1.5mol / l ammonia water; stir again at 25°C in an oil bath, and finally, collect the product by centrifugation, and vacuum dry at 80°C for 8h to obtain composite material A;

[0174] S4-2, then heating the composite material A nanoparticles at 450°C in an inert atmosphere at a rate of 3°C / min, and keeping the temperature constant for 4 hours, and then rapidly cooling at a rate of 15°C / min to prepare composite material B;

[0175] S4-3, dissolve 8 mg of sodium dodecylbenzene sulfonate in 250 mL of deionized water, add 0.1 g of precursor B material, and stir for 45 min; put 0.15 mL of pyrrole into an ice bath at 3°C, and stir for 45 min. At the same time, dissolve 0.35 g of sodium persulfate in 40 mL of distilled water, add it to the pyrrole mixed solution after it is completely dissolved, and stir for 24 h at a reaction temperature below 5°C; at the end of the reaction, collect the product by centrifugation, wash it with distilled water and ethanol in turn to remove impurities, and vacuum dry it at 80°C for 15 h to obtain composite material C;

[0176] S4-4. Finally, the composite material C was calcined at 700°C for 5 h in an argon atmosphere and then rapidly cooled at a rate of 15°C / min to obtain a composite material D coated with a nitrogen-doped carbon layer;

[0177] S4-5. Finally, the nickel oxide layer in the composite material D was removed with 5 mol / l hydrochloric acid, the material was washed with deionized water to neutrality, and vacuum dried at 60°C for 20 hours to form a chestnut-shaped carbon layer to obtain the final product, an encapsulated core-chestnut shell structured silicon-tin composite material, the structural schematic diagram of which is shown in FIG. Figure 1 shown.

[0178] Example 2

[0179] The difference from Example 1 is that in step S0, methyl silane orthosilicate, 0.1 mol / l oxalic acid aqueous solution, phytic acid and triethyl borate are in a mass ratio of 40:0.3:3:1.

[0180] Example 3

[0181] The difference from Example 1 is that the silicon source in step S0 is ethyl orthosilicate.

[0182] Example 4

[0183] The difference from Example 1 is that in step S0, the phosphorus source is phosphoric acid.

[0184] Example 5

[0185] The difference from Example 1 is that in step S0, the boron source is boric acid.

[0186] Example 6

[0187] The difference from Example 1 is that the surfactant in step S1-1 is alkyl dimethyl benzyl ammonium bromide.

[0188] Example 7

[0189] The difference from Example 1 is that all nitrogen sources are melamine.

[0190] Example 8

[0191] The difference from Example 1 is that the heat treatment temperature in step S1-5 is 600°C.

[0192] Example 9

[0193] The difference from Example 1 is that the amount of the doped porous silicon precursor in step S1-3 is 1.2 mmol.

[0194] Example 10

[0195] The difference from Example 1 is that in step S2, the mass ratio of the polyatom-doped encapsulated porous silicon precursor to the tin source is 90:8.

[0196] Embodiment 11

[0197] The difference from Example 1 is that the ball milling speed in step S2 is 800 r / min.

[0198] Example 12

[0199] The difference from Example 1 is that the inert gas in step S2 is helium.

[0200] Embodiment 13

[0201] The difference from Example 1 is that 1.3 mmol of tin-doped carbon encapsulated porous silicon precursor is added in step S3-3.

[0202] Embodiment 14

[0203] The difference from Example 1 is that the heat treatment temperature in step S3-5 is 600°C.

[0204] Embodiment 15

[0205] The difference from Example 1 is that in step S4-1, the quaternary ammonium salt is octadecyltrimethylammonium chloride.

[0206] Example 16

[0207] The difference from Example 1 is that the initiator in step S4-1 is potassium persulfate.

[0208] Embodiment 17

[0209] The difference from Example 1 is that the anionic surfactant in step S4-3 is sodium α-olefin sulfonate.

[0210] Embodiment 18

[0211] The difference from Example 1 is that pyrrole is replaced by pyridine in step S4-3.

[0212] Embodiment 19

[0213] The difference from Example 1 is that the first pyrolysis temperature in step S4-2 is 400°C.

[0214] Embodiment 20

[0215] The difference from Example 1 is that the second pyrolysis temperature in step S4-4 is 750°C.

[0216] Embodiment 21

[0217] The difference from Example 1 is that the porous silicon is replaced by silicon without a porous structure.

[0218] Embodiment 22

[0219] The difference from Example 1 is that there is no phosphorus source in step 1.

[0220] Embodiment 23

[0221] The difference from Example 1 is that there is no boron source in step 1.

[0222] Embodiment 24

[0223] The difference from Example 1 is that the heat treatment temperature in step S3-5 is 450°C.

[0224] Embodiment 25

[0225] The difference from Example 1 is that the heat treatment temperature in step S3-5 is 800°C.

[0226] Embodiment 26

[0227] The difference from Example 1 is that the first pyrolysis temperature in step S4-2 is 350°C.

[0228] Embodiment 27

[0229] The difference from Example 1 is that the first pyrolysis temperature in step S4-2 is 600°C.

[0230] Embodiment 28

[0231] The difference from Example 1 is that the second pyrolysis temperature in step S4-4 is 650°C.

[0232] Embodiment 29

[0233] The difference from Example 1 is that the second pyrolysis temperature in step S4-4 is 850°C.

[0234] The difference from Example 1 is that it is pure silicon powder.

[0235] Comparative Example 2:

[0236] The difference from Example 1 is that only step S0 and step S1 are included.

[0237] Comparative Example 3:

[0238] The difference from the first embodiment is that there is only step S0.

[0239] Comparative Example 4:

[0240] The difference from Example 1 is that the tin-free layer is introduced

[0241] Comparative Example 5:

[0242] The difference from Example 1 is that there is no step S4

[0243] Comparative Example 6

[0244] The difference from Example 1 is that the first coating layer is absent.

[0245] Comparative Example 7

[0246] The difference from Example 1 is that the second coating layer is absent.

[0247] Effect Example 1

[0248] The physical and chemical properties of the silicon-tin composite materials prepared in the examples and comparative examples were tested by conventional methods in the art. The test results are shown in Table 1.

[0249] The element content was tested by XRF method. The microwave digestion method was used. 6±0.5g of the products obtained in Examples 1-31 and Comparative Examples 1-7 were mixed with 2±0.05g of stearic acid and ground. After tableting, Avio TM 200 devices measured.

[0250] Conductivity by Orion Star TM Measured by A212 conductivity benchtop tester.

[0251] The pore size was measured by a POROLUX Cito instrument.

[0252] The D50 was obtained using MS3000 particle size analysis instrument.

[0253] The charge transfer resistance was measured by electrochemical impedance spectroscopy (CEMS) using a blue electric system (compacted density 1.65 g / cm 3 ).

[0254] The above-mentioned test method was used to test Examples 1-29 and Comparative Examples 1-7. The test results are shown in Table 1.

[0255] Table 1

[0256]

[0257]

[0258]

[0259] Effect Example 2

[0260] The preparation method of the button cell used for testing the electrochemical performance is as follows: the silicon-tin composite material prepared in the embodiment and the comparative example is mixed evenly with the conductive agent (KS-6), CMC, and SBR according to 95.5:1.5:1.5:1.5, and coated on a copper foil (thickness of 11±2 μm; width of 14±1 cm), and the compaction density is 1.60 g / cm 3 , vacuum dried and used as the negative electrode, lithium metal as the counter electrode, 1M LiPF6 as the electrolyte, ethylene carbonate (EC) as the solvent, dimethyl carbonate (DMC) as the additive, a mixture of EC and DMC in a mass ratio of 1:1, and a PE / PP / PE composite film as the separator, which can be assembled into a button battery.

[0261] The test conditions are:

[0262] (1) First discharge specific capacity and first effect

[0263] The test method of discharge capacity is: charge to 2V at 0.1C constant current, discharge to 5mV at 0.1C constant current, and the obtained capacity is the discharge capacity;

[0264] The test method for charging capacity is: discharge at 0.1C constant current to 5mV, and the capacity obtained at 0.1C is the charging capacity;

[0265] The first effect can be calculated by the following formula:

[0266] First effect = discharge capacity / charge capacity.

[0267] The first discharge specific capacity and first efficiency of Examples 1-29 and Comparative Examples 1-7 were tested using the above test method. The test results are shown in Table 2.

[0268] (2) 200 cycle capacity

[0269] The battery was charged to 2 V at a constant current density of 0.1 C, and discharged to 5 mV at a constant current of 0.1 C. After 200 cycles, the discharge specific capacity was tested.

[0270] The 200 cycle capacities of Examples 1-29 and Comparative Examples 1-7 were tested by the above test method. The test results are shown in Tables 2 and Figure 2 shown.

[0271] (3) Rate performance

[0272] The rate performance test method is: charge to 2V at 0.1C constant current, discharge to 5mV at 0.1C constant current for 5 cycles, recorded as 0.1C / 0.1C;

[0273] 0.2C / 0.1C, 0.5C / 0.1C, 1C / 0.1C, 2C / 0.1C, 0.1C / 0.1C are tested with the same steps.

[0274] The rate performance of Example 1 was tested by the above test method, and the test results are shown in Table 3 and Figure 3 Shown

[0275] Table 2

[0276]

[0277]

[0278] Table 3

[0279] magnification Capacity retention rate 0.1C / 0.1C 99.5% 0.2C / 0.1C 93.2% 0.5C / 0.1C 86.6% 1.0C / 0.1C 82.8% 2.0C / 0.1C 76.3% 0.1C / 0.1C 98.9%

[0280] Depend on Figure 1 It can be seen that the silicon-tin composite material in Examples 1-29 of the present invention contains a core-shell structure with silicon material as the core, multiple carbon layers and nano-tin particles as the inner coating and chestnut-shaped carbon layers as the outer coating carbon layers. This special structure can alleviate the volume expansion of the silicon material and reduce the resistance of charge transfer. The battery assembled from the silicon-tin composite material has excellent capacity performance (the first discharge specific capacity is more than 2350mAh / g), cycle performance (the capacity retention rate of 200 cycles at a rate of 0.1C is more than 85%) and first efficiency (more than 93.5%).

[0281] Compared with Example 1, Comparative Examples 1-2 directly use silicon powder or tin powder as the negative electrode material, and the charge transfer resistance of the material is significantly improved. Although the initial discharge specific capacity of the obtained lithium-ion battery is relatively high, the 200-cycle capacity at 0.1C is significantly reduced, and the initial coulomb efficiency is greatly reduced. The initial efficiency of Comparative Example 1 is even less than 60%. This may be because when silicon powder or tin powder is used alone as the negative electrode material, the volume expansion is serious, which is very unfavorable to the electrochemical performance of the battery.

[0282] Compared with Example 1, Comparative Example 3 has only one carbon layer as a coating layer, and the charge transfer resistance of the material is significantly improved. Although the initial discharge specific capacity of the obtained lithium-ion battery is relatively high, the 200-cycle capacity at 0.1C is significantly reduced, and the initial coulombic efficiency is also reduced. This may be because when the composite material is used as a negative electrode material, only one carbon layer as a coating layer cannot effectively alleviate the volume expansion, and thus cannot effectively improve the electrochemical performance of the battery. Example 1 has a multi-layer carbon coating structure and heteroatoms are introduced into each layer of carbon, which can multiple guarantee the volume expansion of the silicon material and reduce the impact on lithium ion diffusion and electronic conductivity.

[0283] Compared with Comparative Example 4, tin metal is introduced in Example 1, which can significantly improve electronic conductivity and reduce capacity loss. Tin is melted into nanoparticles multiple times by utilizing its sensitivity to temperature. The reduction in size and the formation of voids between particles further enhance the electronic conductivity and lithium ion diffusion rate of the composite material.

[0284] Compared with Comparative Example 5, the chestnut-shaped structure introduced in Example 1 significantly increases the diffusion pathway of lithium ions, so that the electrolyte can quickly and evenly infiltrate the interior of the material, which plays a role in improving the rate performance after multi-layer coating.

[0285] Compared with Comparative Example 6, the first coating layer in Example 1 can alleviate the volume expansion of the silicon material, and the introduction of heteroatoms enhances the synergistic effect therebetween, thereby improving the electronic conductivity.

[0286] Compared with Comparative Example 7, the second coating layer in Example 1 can further alleviate the volume expansion of the silicon material and tin, thereby obtaining better first efficiency and rate performance.

[0287] Although the specific embodiments of the present invention are described above, it should be understood by those skilled in the art that this is only for illustration and the protection scope of the present invention is defined by the appended claims. Various changes or modifications may be made to these embodiments, but these changes and modifications all fall within the protection scope of the present invention.

Claims

1. A silicon-tin composite material, characterized in that: It includes, from the inside to the outside, a core, a first coating layer, a second coating layer, a third coating layer and a fourth coating layer; the core contains silicon material, the first coating layer is a carbon layer, the second coating layer contains nano-tin particles, the third coating layer is a carbon layer, and the fourth coating layer is a chestnut-shaped carbon layer.

2. The silicon-tin composite material according to claim 1, characterized in that The silicon-tin composite material satisfies one or more of the following conditions (1)-(7): (1) The silicon material is a porous silicon material, such as a mesoporous silicon material; (2) The silicon material is doped with heteroatoms, such as one or more of boron, phosphorus, nitrogen, sulfur and metal heteroatoms; (3) The first coating layer is doped with heteroatoms, such as one or more of nitrogen, boron and phosphorus; (4) The fourth coating layer is doped with heteroatoms, such as one or more of nitrogen, boron and phosphorus; (5) The pore size of the silicon-tin composite material is 12-21 nm; (6) The electrical conductivity of the silicon-tin composite material is 2.5×10 3 -2.7×10 4 S / m; (7) The charge transfer internal resistance of the silicon-tin composite material is 14-28Ω.

3. The silicon-tin composite material according to claim 1, characterized in that: The silicon-tin composite material satisfies one or more of the following conditions (1)-(7): (1) The silicon content in the silicon-tin composite material is 42%-48%, where the percentage is the mass percentage of silicon element in the silicon-tin composite material; (2) The tin content of the silicon-tin composite material is 12%-17%, where the percentage is the mass percentage of the tin element in the silicon-tin composite material; (3) The carbon content of the silicon-tin composite material is 25%-30%, where the percentage is the mass percentage of carbon element in the silicon-tin composite material; (4) The nitrogen content in the silicon-tin composite material is 0%-2%, where the percentage is the mass percentage of nitrogen in the silicon-tin composite material; (5) The boron content in the silicon-tin composite material is 0%-1%, where the percentage is the mass percentage of the boron element in the silicon-tin composite material; (6) The phosphorus content in the silicon-tin composite material is 0%-0.5%, where the percentage is the mass percentage of phosphorus in the silicon-tin composite material; (7) The oxygen content in the silicon-tin composite material may be 7%-14%, where the percentage is the mass percentage of oxygen element in the silicon-tin composite material.

4. A method for preparing the silicon-tin composite material according to any one of claims 1 to 3, characterized in that: It includes the following steps: S1, coating a carbon layer on the surface of a silicon material to obtain a first precursor; S2, mixing the first precursor and a tin source to obtain a second precursor; S3, coating the surface of the second precursor with a carbon layer, and forming nano-tin particles from the tin source during the formation of the carbon layer, to obtain a third precursor; S4. Coating a chestnut-shaped carbon layer on the surface of the third precursor.

5. The method for preparing the silicon-tin composite material according to claim 4, characterized in that: In step S1, a carbon layer is coated on the surface of a silicon material by a solvent gel method, comprising the following steps: S1-1, ultrasonically dispersing a surfactant in water to form spherical micelles; preferably, the surfactant is one or more of hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dialkyldimethylammonium chloride and alkyldimethylbenzylammonium bromide; S1-2, adding a carbon source monomer, a nitrogen source and a catalyst, stirring to obtain a sol; preferably, the molar ratio of the carbon source monomer, the nitrogen source and the catalyst to the surfactant described in step S1-1 is (1.0-3.0): (0.01-0.09): (0.007-0.03): (0.2-0.65); preferably, the nitrogen source is one or more of p-nitroaniline, melamine, triethylamine, pyridine, azobis(ethylbutyronitrile) and pyrrole; preferably, the carbon source monomer includes resorcinol and formaldehyde; preferably, the catalyst is an alkaline compound, such as one or more of sodium carbonate, sodium hydroxide and sodium citrate; S1-3, adding silicon material to obtain a core-shell colloid; preferably, the molar ratio of the silicon material to the catalyst in step S1-2 is (0.8-1.5): (0.007-0.03); S1-4, heating and polymerizing to obtain a silicon material coated with a gel polymer; preferably, the polymerization temperature is 80-100° C.; preferably, the polymerization time is 3-8 hours; S1-5, carbonization, gel polymer forms a carbon layer; preferably, the carbonization method is heat treatment; wherein the temperature of the heat treatment is preferably 450-800°C, and the time of the heat treatment is preferably 4-10h; preferably, a drying step is also included before the carbonization step in step S1-5; And / or, before step S1, the method further includes: S0, preparing a porous silicon material; wherein the porous silicon material is preferably prepared by a sol-gel method and a magnesium thermal reduction method.

6. The method for preparing the silicon-tin composite material according to claim 4, characterized in that: The method for preparing the silicon-tin composite material satisfies one or more of the following conditions (1)-(3) in step S2: (1) The mass ratio of the first precursor to the tin source is (85-95): (8-15); (2) The tin source is tin powder and / or tin dioxide powder; (3) The mixing method is ball milling; preferably, the ball milling is carried out in the presence of an inert gas plasma; preferably, the inert gas is one or more of argon, helium, and neon; preferably, the ambient pressure of the ball mill is 0.1 MPa; preferably, the ball-to-material ratio of the ball mill is (40-60):1; preferably, the rotation speed of the ball mill is 650-800 r / min; preferably, the ball milling time is 4-8 h; preferably, the tube volume of the ball mill is 0.2 L; preferably, the working current of the ball mill is 1-3 A; preferably, the excitation voltage of the ball mill is 10-25 kV.

7. The method for preparing the silicon-tin composite material according to claim 4, characterized in that: In step S3, a carbon layer is coated on the surface of the second precursor by a solvent gel method, comprising the following steps: S3-1, ultrasonically dispersing a surfactant in water to form spherical micelles; preferably, the surfactant is one or more of hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dialkyldimethylammonium chloride and alkyldimethylbenzylammonium bromide; S3-2, adding a carbon source monomer, a nitrogen source and a catalyst, stirring to obtain a sol; preferably, the molar ratio of the carbon source monomer, the nitrogen source and the catalyst to the surfactant in step S3-1 is (1.0-3.0): (0.01-0.09): (0.007-0.03): (0.2-0.65); preferably, the nitrogen source is one or more of p-nitroaniline, melamine, triethylamine, pyridine, azobisethylbutyronitrile and pyrrole; preferably, the carbon source monomer includes resorcinol and formaldehyde; preferably, the catalyst is an alkaline compound; more preferably, the alkaline compound is one or more of sodium carbonate, sodium hydroxide and sodium citrate; S3-3, adding the second precursor to obtain a core-shell colloid; preferably, the molar ratio of the second precursor to the catalyst described in step S3-2 is (0.8-1.5): (0.007-0.03); S3-4, heating and polymerizing to obtain a second precursor coated with a gel polymer; preferably, the polymerization temperature is 80-100° C.; preferably, the polymerization time is 3-8 hours; S3-5, carbonization, the gel polymer forms a carbon layer, the tin source forms tin nanoparticles, and a third precursor is obtained; preferably, the carbonization method is heat treatment; wherein the temperature of the heat treatment is preferably 450-800°C; the time of the heat treatment is preferably 4-10h; preferably, a drying step is also included before the carbonization step in step S3-5.

8. The method for preparing the silicon-tin composite material according to claim 4, characterized in that: In step S4, a chestnut-shaped carbon layer is coated on the surface of the third precursor by a chemical bath deposition method, comprising the following steps: S4-1, ultrasonically dispersing the third precursor in a quaternary ammonium salt aqueous solution to obtain a third precursor dispersion; adding an aqueous solution containing a nickel salt and an initiator to the third precursor dispersion, stirring, adding ammonia water, reacting under stirring, and centrifugation drying to obtain a composite material A; preferably, the mass ratio of the third precursor to the quaternary ammonium salt is (0.1-0.5): (0.009-0.05); preferably, the nickel salt is one or more of nickel acetate, nickel nitrate and nickel sulfate; preferably, the initiator is one or more of potassium persulfate, sodium persulfate and potassium hydrogen persulfate; preferably, the mass ratio of the nickel salt, the initiator and the third precursor is (0.1-0.5): (0.02-0.1): (0.1-0.5); S4-2, heat-treating the composite material A and then rapidly cooling it to obtain a composite material B; preferably, the temperature of the heat treatment is 350-600°C; preferably, the constant temperature time of the heat treatment is 2-5h; preferably, the heating rate of the heat treatment is 1-10°C / min; preferably, the cooling rate of the rapid cooling is 15°C / min; S4-3, adding the composite material B to a surfactant aqueous solution, and adding a carbon source monomer and an initiator in sequence, reacting under stirring, centrifuging, washing and drying to obtain a composite material C; preferably, the surfactant is an anionic surfactant; more preferably, the anionic surfactant is one or more of sodium dodecylbenzenesulfonate, hexadecyltrimethylammonium p-toluenesulfonate, sodium dodecylsulfonate and sodium α-olefinsulfonate; preferably, the initiator is one or more of potassium persulfate, sodium persulfate and potassium hydrogen persulfate; preferably, the mass ratio of the surfactant, the carbon source monomer and the initiator is (3-10): (0.09-0.3): (0.2-0.65); preferably, the carbon source monomer is pyrrole and / or pyridine; S4-4, calcining the composite material C, cooling, and obtaining a composite material D; the composite material D comprises a nickel layer and a carbon layer; preferably, the calcination temperature in step S4-4 is 650-850°C; preferably, the calcination time is 3-6h; preferably, the calcination is carried out in an inert atmosphere; preferably, the cooling rate of the cooling is 15°C / min; S4-5, treating the composite material D with acid to remove the nickel layer, washing, and drying to form a chestnut-shaped carbon layer; Preferably, the acid used in the acid treatment is one or more of hydrochloric acid, sulfuric acid and nitric acid; Preferably, the concentration of the acid used in the acid treatment is 0.05-0.2 mol / L.

9. A pole piece, comprising the silicon-tin composite material according to any one of claims 1 to 3.

10. A battery comprising the pole piece according to claim 9.

Citation Information

Patent Citations

  • Preparation method of lithium ion battery negative electrode material with double-layer shell structure

    CN116565175A